Share price reaction to dividend announcements in Bursa Malaysia surrounding the COVID-19 period - Chen, Wan Chuen (2024)
The general objective of this study is to investigate the share price reaction towards dividend announcement in Bursa Malaysia before, during and after COVID-19 periods. Dividend signalling theory, efficient market hypothesis and behavioural finance hypothesis are applied with effect of health crisis being taken into account. To examine the validity of dividend theories, event study methodology is employed. The results showed that dividend signalling theory holds before and during COVID-19 periods, but the theory hold at certain level after health crisis. It is also found that there is leakage of insider information before dividend is announced.